HPG-Dependent Peri-Pubertal Regulation of Adult Neurogenesis in Mice - Sara Trova; Sara Trova; Serena Bovetti; Giuliana Pellegrino; Sara Bonzano; Paolo Giacobini; Paolo Peretto (Frontiers Media S.A., 2020)
Adult neurogenesis, a striking form of neural plasticity, is involved in the modulation of social stimuli driving reproduction. Previous studies on adult neurogenesis have shown that this process is significantly modulated around puberty in female mice. Puberty is a critical developmental period triggered by increased secretion of the gonadotropin releasing hormone (GnRH), which controls the activity of the hypothalamic-pituitary-gonadal axis (HPG). Secretion of HPG-axis factors at puberty participates to the refinement of neural circuits that govern reproduction. Here, by exploiting a transgenic GnRH deficient mouse model, that progressively loses GnRH expression during postnatal development (GnRH::Cre;DicerloxP/loxPmice), we found that a postnatally-acquired dysfunction in the GnRH system affects adult neurogenesis selectively in the subventricular-zone neurogenic niche in a sexually dimorphic way. Moreover, by examining adult females ovariectomized before the onset of puberty, we provide important evidence that, among the HPG-axis secreting factors, the circulating levels of gonadal hormones during pre-/peri-pubertal life contribute to set-up the proper adult subventricular zone-olfactory bulb neurogenic system.